2006
DOI: 10.7326/0003-4819-145-5-200609050-00006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyphenols in Olive Oil on Heart Disease Risk Factors

Abstract: Olive oil is more than a monounsaturated fat. Its phenolic content can also provide benefits for plasma lipid levels and oxidative damage. International Standard Randomised Controlled Trial number: ISRCTN09220811.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
456
14
14

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 674 publications
(536 citation statements)
references
References 38 publications
25
456
14
14
Order By: Relevance
“…An international study with a large sample size has been conducted on humans (Covas et al, 2006) but not, to our knowledge, on animals.…”
Section: Blood Analysesmentioning
confidence: 99%
“…An international study with a large sample size has been conducted on humans (Covas et al, 2006) but not, to our knowledge, on animals.…”
Section: Blood Analysesmentioning
confidence: 99%
“…The beneficial effects of olive oil are mainly attributed to polyphenols, in particular the antioxidant action. These compounds can exert an antioxidant effect in vivo, in particular in the postprandial phase according to Bonanome et al 48 They are also considered as dietary nutrients of the Mediterranean diet 49 . According to a study carried out by a European group, two oils were tested: a virgin olive oil very rich in polyphenols (366 mg/kg), a mixed oil obtained from a mixture of virgin olive oil, Refined olive oil, moderately rich in polyphenols (164 mg/kg), showed that olive oil rich in polyphenols exhibits antioxidant action and increases HDL-cholesterol 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The European Study of the Antioxidant Effects of Olive Oil and its Phenolic Compounds on lipid oxidation (EUROLIVE) study (Covas et al, 2006) was a clinical trial to evaluate the effects of the phenolic content in olive oil on the plasma lipid profile and lipid oxidative damage. The systemic markers of lipid oxidation decreased inversely with the phenolic content of the olive oil (particularly low density lipoprotein (LDL) oxidation markers) and high density lipoprotein (HDL) cholesterol levels increased in a direct relationship with the phenolic content of the olive oil.…”
Section: The Mediterranean Diet's Effect On Oxidation and Inflammatiomentioning
confidence: 99%